2014
DOI: 10.1093/jrr/rrt235
|View full text |Cite
|
Sign up to set email alerts
|

The clinical outcome of intracranial hemangioblastomas treated with linac-based stereotactic radiosurgery and radiotherapy

Abstract: Recent publications have reported stereotactic radiosurgery as an effective and safe treatment for intracranial hemangioblastomas. However, because of the low incidence of these particular tumors, reports on large patient number studies have not yet been available. The objective of this study was to analyze the clinical results of 14 patients with 56 intracranial hemangioblastomas treated with linear accelerator (linac)-based stereotactic radiosurgery (SRS) and radiotherapy (SRT) in the same institute. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The progression-free survival after SRS at 1 year, 3 years, and 5 years was 96.9%, 95.0%, and 89.9% (7). The 1-year, 2-year, and 6-year local control rates after treatment with linear acceleratorebased SRS and stereotactic radiotherapy such as CyberKnife (Accuray, Sunnyvale, California, USA) and X-Knife were 98% (1 year), 88% (2 years), and 73% (6 years) (9). SRS was more effective for patients with VHL disease than for patients with sporadic hemangioblastomas; 5-year and 10-year tumor control rates were 67% and 44% for patients with sporadic hemangioblastomas and 97% and 83% for patients with VHL disease (4).…”
Section: Treatment Strategies For Cerebellar Hemangioblastomas: Simplmentioning
confidence: 99%
“…The progression-free survival after SRS at 1 year, 3 years, and 5 years was 96.9%, 95.0%, and 89.9% (7). The 1-year, 2-year, and 6-year local control rates after treatment with linear acceleratorebased SRS and stereotactic radiotherapy such as CyberKnife (Accuray, Sunnyvale, California, USA) and X-Knife were 98% (1 year), 88% (2 years), and 73% (6 years) (9). SRS was more effective for patients with VHL disease than for patients with sporadic hemangioblastomas; 5-year and 10-year tumor control rates were 67% and 44% for patients with sporadic hemangioblastomas and 97% and 83% for patients with VHL disease (4).…”
Section: Treatment Strategies For Cerebellar Hemangioblastomas: Simplmentioning
confidence: 99%
“…The utility of radiosurgery and image-guided systems has been further supported by case series, which continue to show favorable outcomes. 1,5,7,9,10,17,[20][21][22] Furthermore, a recent systematic review surveying 10 papers that discussed radiosurgical treatment for intramedullary spinal tumors revealed that the CyberKnife (Accuray) was used in 87% of cases and afforded favorable clinical and radiological outcomes. 8 We present a large prospective cohort of spinal hemangioblastomas treated with radiosurgery.…”
mentioning
confidence: 99%
“…25 . 28 Surgical resection is also the best treatment for orbital schwannomas. Subciliary approach is the most preferred method for the masses inferior and medial to the optic nerve.…”
Section: Discussionmentioning
confidence: 99%